Study of the potentiometric response of the doped spinel Li1.05Al0.02Mn1.98O4 for the optimization of a selective lithium ion sensor - Freitas, Bruno H. [UNESP]; Amaral, Fabio A.; Bocchi, Nerilso; Teixeira, Marcos F. S. [UNESP] (Pergamon-Elsevier B.V. Ltd, 2010)
In this paper, we studied the development of a selective lithium ion sensor constituted of a carbon paste electrode modified (CPEM) with an aluminum-doped spinel-type manganese oxide (Li1.05Al0.02Mn1.98O4) for investigating the influence of a doping ion in the sensor response. Experimental parameters, such as influence of the lithium concentration in the activation of the sensor by cyclic voltammetry. pH of the carrier solution and selectivity for Li+ against other alkali and alkaline-earth ions were investigated. The sensor response to lithium ions was linear in the concentration range 5.62 x 10(-5) to 1.62 x 10(-3) mol L-1 with a slope 100.1 mV/decade over a wide pH 10 (Tris buffer) and detection limit of 2.75 x 10(-5) mol L-1, without interference of other alkali and alkaline-earth metals, demonstrating that the Al3+ doping increases the structure stability and improves the potentiometric response and sensitivity of the sensor. The super-Nernstian response of the sensor in pH 10 can be explained by mixed potential arising from two equilibria (redox and ion-exchange) in the spinel-type manganese oxide. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Potentiometric ion sensors; Lithium ions; Doped manganese oxide; Electrochemical properties